Is a Post-philosophical Sociology Possible? Insights from Norbert Elias's Sociology of Knowledge. (March 2014) - Walsh, Philip
This article investigates the status of Norbert Elias's conception of the sociology of knowledge as the means to provide a new epistemological security for sociology. The author of the article argues that this translates into an effective critique of the underlaboring model of the relationship between philosophy and the social sciences, which is consistent with Elias's attempt to consolidate his own sociological theory. Nevertheless, the author argues that Elias's sociology of knowledge runs into problems in its attempt to evade the problem of relativism in explanation, and in its conception of human agency.